The Potential Role of Klotho as a Prognostic Biomarker in Deceased Donor Kidney Transplantation. (July 2018) - Kim, Suh Min; Kim, Sang Joon; Ahn, Sanghyun; Min, Sang-Il; Min, Seung-Kee; Ha, Jongwon
Abstract : Introductions: Klotho, first known as an 'aging suppressor' factor, is produced in renal tubular epithelial cells and acts as co-receptor for fibroblast growth factor-23. It has been reported to decrease in animal model of acute kidney injury. In humans, klotho is down-regulated in patients with chronic kidney disease, however, the report on expression after kidney transplantation is limited. We measured the expression of klotho in kidney transplant donors and analyzed the effect of it on the clinical outcomes of transplants. Patients and Methods: Thirty-one patients, who underwent deceased donor kidney-only transplantation between March 2015 and October 2016, were enrolled. The blood samples and kidney biopsy tissues of donors were prospectively collected. The expressions of klotho were measured with ELISA and immunohistochemistry stain. Clinical outcomes of transplants were evaluated by the change of glomerular filtration rates (GFR) and incidence of delayed graft functions (DGF) and acute rejection (AR). Results: We divided the patients into two groups according to the expression of klotho in donor blood (median 497.8 pg/ml, range 157.6~1719.3): low (<500 pg/ml) and high (>500 pg/ml) klotho group. There is no significant difference in recipients` characteristics. In donor factors, the serum level of final creatinine at procurement was statistically significantly higher in high klotho group (0.75±0.31 vs 1.18±0.60 mg/dL, P = 0.021) and there is a tendency to lower Kidney Donor Risk Index (KDRI) in high klotho group. After transplants, the incidences of DGF and AR were similar in two groups. Glomerular filtration rates at 12 months after transplants were significantly higher in high klotho groups (47.0±16.0 vs. 61.5±18.0 0 mL/min/1.73m2, P= 0.029). In pathologic analysis, the patients in high klotho group showed a tendency to less interstitial fibrosis, although it could not reach statistical significance. When analyzed the expression of klotho in kidney tissues of donors, GFR was much improved with up-regulated expression of klotho in tissues. There was no correlation between klotho expression and glomerulosclerosis, interstitial fibrosis and tubular atrophy in kidney tissues of donors. Conclusions: Our data demonstrated that recipients received the graft from donors with higher expression of klotho showed much improved GFR at 1-year after transplants, although the donors had higher creatinine levels at procurements and lower KDRI. Klotho expression in donors could be a new good independent predictor for transplants outcomes in deceased donor kidney transplantation.